Hubungan Tingkat Pengetahuan dengan Sikap dan Tindakan terhadap Human Immunodeficiency Virus/ Acquired Immunodeficiency Syndrome pada Remaja - Sitepu, Jenny Novina (Nommensen Journal of Medicine, 2021)
Background: Human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) is one of the diseases with high mortality rate, but we can prevent its transmission. People with good knowledge about HIV/AIDS should have the positive attitude and action on HIV/AIDS. Objective: The aim of this study was to investigate the correlation between knowledge level about HIV/AIDS and the attitude and action on HIV/AIDS in high school students. Methods: This cross-sectional study of 96 teenagers (aged 15-19 years old) was performed at SMA Swasta HKBP Sidorame Medan. The knowledge, attitude, and action on HIV/AIDS were evaluated with questionnaire. Knowledge level was categorized to good, fair, and bad. Attitude was categorized to positive and negative attitude. Action was categorized to risk and no risk action. Likelihood-ratio test was performed to evaluate the correlation between knowledge with attitude and action on HIV/AIDS because chi-square test criteria was not met. Results: This study showed that about 57.3% of students have bad knowledge about HIV/AIDS, 62.5% have positif attitude on HIV/AIDS, and 86.5% did no risky action on HIV/AIDS. Likelihood-ratio test showed that there was a significant correlation between knowledge about HIV/AIDS with attitude on HIV/AIDS (p= 0.000), and with the action on HIV/AIDS (p= 0.009). Conclusion: The knowledge level about HIV/AIDS correlates with attitude and action on HIV/AIDS.